Cyclic and postcyclic behaviour of silts and silty sands from the Indo Gangetic Plain. Issue 125 (October 2019) - Varghese, Ramon; Senthen Amuthan, M.; Boominathan, A.; Banerjee, Subhadeep
Abstract: The Indo Gangetic Plain (IGP) that lies on the verge of subduction zone of Indian and Eurasian plate is a seismically active, densely populated region with deep soil deposits. A number of critical structures such as rail and highway bridges and nuclear power plants are being built in the region to cater to the large population of the region, and hence the characterization of deep soil deposits in this region are important. In the present study undisturbed soil samples (UDS) from a site in the IGP plane are examined for static, cyclic, and post-cyclic behaviour. The soils tested have fines content varying from about 20% to 80%, and the fines are non-plastic in nature. The modulus reduction and damping ratio of soil at small, medium and large strain range is examined with the UDS by carrying out bender element, resonant column, and cyclic triaxial tests, respectively. Post cyclic behaviour of non-plastic silty soils is also examined with single stage and multistage cyclic triaxial testing. It is observed that the post-cyclic shear strength increases with increase in the non-plastic fines in the soil. The history of cyclic loading preceding the post cyclic tests is found to influence the tangent modulus observed in post cyclic tests. A site specific calibration parameter is proposed to predict pore pressure response using the energy based Green Mitchel Polito (GMP) pore pressure model. Highlights: The modulus degradation and damping curves for silty deposits of the Indo Gangetic Plain are proposed. The post cyclic stress strain behavior of silty soils is found to be heavily influenced by the fines content. The dependence of post cyclic stiffness, on the stiffness reduction during cyclic loading is evident. Importance of experimental calibration of the GMP pore pressure model is evident.